al-Ittijah al-Sufi fi al-Tafsir - Harda Armayanto (Tasfiyah: Jurnal Pemikiran Islam, 2018)
This article discusses Sufi objectives in the interpretation of al-Qur'an. The Sufi interpretation nomenclature itself has many variants; some call it tafsir isyariy, tafsir bathiniy, tafsir faidhiy, etc. The Moslem scholars have different view on the kinds of the interpretation; some of them accept it and some refuse it. Those who refuse it usually equate the interpretation with the tafsir bathiniy which is mostly carried out by Shia’s followers. By referring to several books of experts in the field of ulûm al-Qur'an, the authors find that there are differences between Sufi interpretations and tafsir bathiniy. The difference can be referred to the purpose of each interpretation. This article discusses it and the purpose of each interpretation, so it is found that Sufi interpretation is not kind of tafsir bathiniy.